Platform design methodology for sustainable product-service development - Ho, Addison Yu Ann (2019)
Exchange of ideas and evolving perspectives on how we view resources today has led to a propulsion for focus in strategies to design for sustainability especially in product development and management. One of these key strategies is to create a product-service system. A product-service system generally encapsulates the idea of bundling of both aspect of product and service, to deliver a cohesive and collaborated consumption in the fulfillment of customers’ needs while attaining pro-sustainability outcomes. While much emphasis in past literature has used to develop product family, servitization development is limited within a product-service system especially in introductory outcomes for personalization and user-centric design. Through platform methodology, this project discusses an extended possible framework of bundling product, service, and smart system ideology using a three-dimensional approach to discuss the possibility of creating a product-service system within a family of aircraft seats identified as a case study. In discussing sustainability, this project further investigates the extension of grey rationality analysis using a triangulation method proposed for environmental, economic and social pertaining to a more fluid and volatile service design as compared to robust product family design. Commonality analysis also is highlighted to determine a sustainable outcome – High sustainability performance and high commonality.